Outcomes of Covid-19 Disease in Cirrhotic and Non-Cirrhotic Patients - Namra Shakoor, Namra Rasheed, Abida Rehman (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study is to evaluate whether there is a difference in poor outcomes between cirrhotic and non-cirrhotic individuals who have been diagnosed with coronavirus infection. Study Design: Retrospective/cohort study Place and Duration: Study was conducted at PHFMC (ZCD QADIR BAKHASH,Toba Tek Singh) within a duration of July 2020-Dec2021. Methodology: There were 140 participants in all, including men and women with or without chronic liver disease. This study included people aged 18 to 70. Two groups of patients were formed. With cirrhosis, 70 individuals are in group I, while the rest are in group II (without cirrhosis 70 patients). The death rates of both groups were compared. Data were analyzed using SPSS 24.0. Results: In group I, there were 40 men (57.1%) and 30 women (42.9%) with an average age of 41.9±8.35 years, whereas in group II, there were 45 men (64.3%) and 25 women (35.7 percent) with an average age of 45.11±7.41 years. With p-value 0.05, we discovered that mortality rates among patients in group I (cirrhotic) were significantly higher than those of patients in group II (non-cirrhotic) with mortality rates of 25 and 8 respectively. Conclusion: We came to the conclusion that the incidence of poor outcomes was considerably higher among cirrhotic patients with coronavirus illness as compared to non-cirrhotic individuals in our research.